2003
DOI: 10.1074/jbc.m204716200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Regulation of Mitogen-activated Protein Kinases and p27Kip1 in Smooth Muscle Cells from Different Vascular Beds

Abstract: Excessive proliferation and migration of vascular smooth muscle cells (SMCs) participate in atherosclerotic plaque growth. In this study, we investigated whether SMCs from vessels with different atherogenicity exhibit distinct growth and migratory potential and investigated the underlying mechanisms. In fat-fed rabbits, we found increased cell proliferation and atheroma formation in the aortic arch versus the femoral artery. When examined in culture, SMCs isolated from the aortic arch (ASMCs) displayed a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 53 publications
3
34
0
Order By: Relevance
“…Indeed, in a previous study, overexpression of p27 kip1 was reported to inhibit VSMC growth (74). Here, we show that whereas all three agonists (PDGF-BB, TNF-␣, and IGF-1) induced phosphorylation and nuclear exclusion in VSMC, only PDGF-BB had a significant inhibitory effect on p27 kip1 .…”
Section: Discussionmentioning
confidence: 42%
“…Indeed, in a previous study, overexpression of p27 kip1 was reported to inhibit VSMC growth (74). Here, we show that whereas all three agonists (PDGF-BB, TNF-␣, and IGF-1) induced phosphorylation and nuclear exclusion in VSMC, only PDGF-BB had a significant inhibitory effect on p27 kip1 .…”
Section: Discussionmentioning
confidence: 42%
“…The protective role of p27 kip1 against neointimal thickening has been also demonstrated in hypercholesterolemic apolipoprotein-deficient mice in which genetic inactivation of one or both p27 kip1 alleles shows progressively accelerated atherosclerosis (56,69,70). The migratory response exhibited by VSMC in response to mitogens has been shown to be inhibited by overexpression of p27 kip1 (58,67,71,72). Inhibition of VSMC proliferation by salicylate has also been shown to be mediated by up-regulation of p27 kip1 and p21 (73).…”
Section: Fig 5 Heparin Treatment Of Vsmc Increases the Half-life Ofmentioning
confidence: 85%
“…Although not tested in this work, the MAPK pathway has been shown to have effect on cellular p27 kip1 levels in VSMC. Pharmacological inhibition of MAPKs increased p27 kip1 expression and attenuated VSMC proliferation and migration (72). MAPK cascade has also shown to be required for p27 kip1 down-regulation and S phase entry in fibroblasts and epithelial cells (80).…”
Section: Fig 5 Heparin Treatment Of Vsmc Increases the Half-life Ofmentioning
confidence: 99%
“…It is possible that p27Kip1 may also be a downstream effector of AGGF1‐ERK signaling. Inhibition of ERK1/2 by specific inhibitors or overexpression of dominant negative ERK inhibits PDGF‐induced downregulation of p27Kip1 61, 62. p27Kip1 is a cyclin‐dependent kinase inhibitor that regulates cell cycle progression and cell proliferation 63.…”
Section: Discussionmentioning
confidence: 99%